PUB opens upgraded waterworks which houses the world's largest ceramic membrane water treatment plant. Issue 10 (October 2019) - Atkinson, Simon
Abstract : PUB, Singapore's National Water Agency that is responsible for ensuring a sustainable and efficient water supply, has unveiled its latest upgraded water treatment plant, which houses the largest ceramic membrane system in the world. Here, in an extended version of the news item that appears in Membrane Technology September 2019 (page 1) – which initially reports the opening of the upgraded facility – we look briefly at the history of the Choa Chu Kang Waterworks, its initial use of membrane technology and related plant upgrades that have been carried out over the years.